Assisted Suicide: A Rational Option or a Tragedy? - Wils, Jean-Pierre (Concilium, 2021)
In the context of the debate about assisted dying, assisted suicide is increasingly coming to the fore. In the Netherlands and Germany there will shortly be a revision of the penal code, and help with suicide is to be expressly allowed. Under this law the autonomy of the person concerned - their right to self-determination in matters relating to death - must be respected. There are no decisive arguments against a demand for assisted suicide, but the one-sided focus on autonomy involves considerable dangers. Suicide should not be glorified as an act of overdue emancipation. It is no enhancement of personal freedom, but a tragedy.